2021
DOI: 10.1108/ajar-09-2020-0086
|View full text |Cite
|
Sign up to set email alerts
|

How financial literacy moderate the association between behaviour biases and investment decision?

Abstract: PurposeThe purpose of the study is to examine the impact of behavioural biases (i.e. overconfidence, risk-aversion, herding and disposition) on investment decisions amongst gender. The authors further examine the moderation effect of financial literacy in the relationship between behaviour biases and investment decisions amongst gender.Design/methodology/approachThe study considered a cross-sectional research design. For this survey, the data have been collected through a structured questionnaire from 253 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
139
7
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(176 citation statements)
references
References 63 publications
13
139
7
17
Order By: Relevance
“…Overconfidence bias is often experienced by novice investors who want to quickly get profits in investing. Research conducted by Adil et al (2021) found that overconfidence bias does not have a significant effect on investment decisions for investors in India. Primary et al (2020) conducted research on the Indonesia Stock Exchange and found that overconfidence bias does not have a significant effect on investment decisions for investors on the Indonesia Stock Exchange.…”
Section: Literature Review 11 Behavioural Biases 1 Overconfidence Biasmentioning
confidence: 94%
See 3 more Smart Citations
“…Overconfidence bias is often experienced by novice investors who want to quickly get profits in investing. Research conducted by Adil et al (2021) found that overconfidence bias does not have a significant effect on investment decisions for investors in India. Primary et al (2020) conducted research on the Indonesia Stock Exchange and found that overconfidence bias does not have a significant effect on investment decisions for investors on the Indonesia Stock Exchange.…”
Section: Literature Review 11 Behavioural Biases 1 Overconfidence Biasmentioning
confidence: 94%
“…Economic theory says that the readiness of an investor is to be rational where they will first evaluate all available information before making a decision (Qasim et al, 2019). Research conducted by Adil et al (2021) stated that there is an effect of herding bias on investors' decisions in taking investments.…”
Section: Herding Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…[21] explained that good financial literacy gave significant differences in financial behavior. Financial literacy helped investors to deny irrelevant information [23], gave an investor the ability to analyze in choosing the financial product [4] and isolated investors from herding behavior [2]. Low levels of financial literacy caused behavioral bias because the decision was influenced more by psychology than by knowledge [18].…”
Section: The Moderating Role Of Financial Literacymentioning
confidence: 99%